Characterization of commensal strains with bacteriocinmediated inhibition against Streptococcus pneumoniae - Solanki, Konil Hasmuk (2022)
Tese de mestrado, Microbiologia Aplicada, 2022, Universidade de Lisboa, Faculdade de Ciências